PENERAPAN METODE PEMODELAN DALAM MENINGKATKAN KEMAMPUAN BERPIDATO SISWA KELAS VI SDN INPRES 1 UJUNA KECAMATAN PALU BARAT - Hadijah, Hadijah (BAHASANTODEA, 2016)
This researh about learning problem in the class with the problem statement is “How is the application of modelling method in improving speech ability of the sixth grade student at SDN Inpres 1 Ujuna ? and what is the application of modelling method can improve speech ability of sixth grade student at SDN Inpres 1 Ujuna?. the purpose of this research is to describe the application of modelling method in improving speech ability of sixth grade student at SDN Inpres 1 Ujuna and to describe speech ability of sixth grade student at SDN Inpres 1 Ujuna in the learning process through modelling method. Genre of this research is a class action research. Design of this research refers at the kurt lewin model which developed by kemmis and Mc. Taggart (2012). There are 4 steps : (a) Planning, (b) Implementing, (c) Observation, and (d) reflection. There are 4 aspects of assesment, they are pronounciation aspect, fluently aspect, material mastery aspect, and expression aspect. Based on the assesment of pronounciation aspect at the cycle I is 14,4 or 80%, fluently aspect is 10,05 or 100%, material mastery aspect is 12,7 or 65% and expression aspect is 12,7 or 70%, whereas at the cycle II at the pronounciation aspect is 20 or 100%, fluently aspect is 19,5 or 100%, material mastery aspect is 15,6 or 95%, nd expression aspect is 15,8 or 85%. Those aspects have improvement from cycle I to cycle II. At the cycle I the average completeness percentage is 65,05 or 35%, and at the cycle II was happen the average completeness percentage tobe 82,3 or 85%. There is an improvement at the learning outcomes of speech after has done speech learning process with using modelling method at the cycle I and cycle II. The students completeness percentage in the speech at the cycle I only achieve 35% with the average score is 65,05 and still less from the standar completeness, that is 70. At the cycle II the completeness percentage was happen improvement to be 85% with the average score 82,3 and already fulfill the completeness standar which decided. The improvement which happen can be seen from the result that get it. That is the percentage is more increase from the cycle I to cycle II.